Surveillance of SARS-CoV-2 Infection in Rodent Populations in Tokyo, Japan - Kuroda, Yudai; Hotta, Akitoyo; Taira, Masakatsu; Koizumi, Nobuo; Tatemoto, Kango; Park, Eun-sil; Virhuez-Mendoza, Milagros; Yamamoto, Tsukasa; Komatsu, Noriyuki; Shibo, Keigo; Sasaki, Takeshi; Mori, Yoshiyuki; et al. (Japanese Journal of Infectious Diseases, 2024)
The persistence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) among wildlife populations poses a potential risk for the emergence of novel variants. Therefore, monitoring SARS-CoV-2 infections in animals is crucial. As urban rodents live in close proximity to human habitats, there is a concern that they may be a potential source of zoonoses. To examine the prevalence of SARS-CoV-2 in rodent populations, we analyzed 128 serum samples and 129 oral swabs collected from 128 brown rats (Rattus norvegicus) and two black rats (Rattus rattus) captured for pest control purposes in Tokyo, Japan, between May and December 2023. A virus-neutralizing test using the omicron variant revealed no evidence of SARS-CoV-2 infection. Real-time reverse transcription- PCR of oral swabs did not detect any SARS-CoV-2 RNA-positive rats. These results indicate a low probability of SARS-CoV-2 circulation among rat populations in Tokyo.